Creativity Factors Analysis of Food Industry Employees in Thailand: - Batrpho, Pansri; Thotongkam, Woraanong; Limpasirisuwan, Natcha; Wimuttisuksuntorn, Warantorn (Journal of Management Science Nakhonratchasima University, 2022)
This article was aimed 1) to analyze the components of the creativity of the employees in the food industry in Thailand, and 2) to define the indicators of the creativity of the employees in the food industry in order to create a guideline for improving the quality of Thailand’s food industry. Data was collected by questionnaires from food industry operators in Thailand and 250 responses were received. The results showed from the factor analysis that the components of the employees’ creativity could be divided into six groups; (1) the cognitive fluidity;4 indicators, (2) the challenging tasks;4 indicators, (3) the freedom in work process;4 indicators, (4) the proactive changes;4 indicators, (5) the continuous learning; 4 indicators, and (6) the constructive connection;4 indicators. The results of the corroborative component analysis, considering the component weight coefficient of the indicators, was also found that there were statistically significant factors weights between 0.760 – 0.916 at the level of .01. The most important variable for the creativity was the constructive connection, followed by the freedom to work, the proactive changes, the continuous learning, the fluidity of new ideas, and the challenging tasks respectively.